2010
DOI: 10.1007/s10658-010-9680-3
|View full text |Cite
|
Sign up to set email alerts
|

Different genes can be responsible for crown rot resistance at different developmental stages of wheat and barley

Abstract: Crown rot, caused by several Fusarium species, is one of the most damaging diseases in wheat and barley. Growing resistant varieties has long been recognised as an integral part in effectively managing the disease. One of the factors hindering the progress of breeding for crown rot resistance is the lack of a reliable and high throughput bioassay that allows rapid and accurate assessment of large numbers of genotypes so that highly susceptible materials can be quickly rejected and potentially resistant lines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…To assess homoeolog expression bias in bread wheat during response to biotic stress, an established laboratory infection assay (Yang et al ., ) was performed to infect wheat seedlings with F. pseudograminearum . Four biological replicates of F. pseudograminearum ( Fp )‐inoculated and noninoculated (mock) wheat plants were sampled as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…To assess homoeolog expression bias in bread wheat during response to biotic stress, an established laboratory infection assay (Yang et al ., ) was performed to infect wheat seedlings with F. pseudograminearum . Four biological replicates of F. pseudograminearum ( Fp )‐inoculated and noninoculated (mock) wheat plants were sampled as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…In barley, loci affecting plant height are also located within the 3HL and 4H QTLs (Li et al ., ). The findings from the studies employing NILs showed that short isolines have stronger FCR resistance than do tall isolines (Ma et al ., ; Yang et al ., ; Zheng et al ., ). In addition, FCR infection seems to spread faster within tall plants, and this phenomenon was explained by the differences observed in cell densities between short and tall genotypes (Bai and Liu, ).…”
Section: Breeding For Fcr Resistance and Tolerancementioning
confidence: 99%
“…The variation among pathogenic isolates associated with the FCR complex has been previously studied by employing various assessment standards of inoculation techniques, including millet seeds, spore suspension and agar plugs (Akinsanmi et al, 2004;Fernandez and Chen, 2005;Smiley et al, 2005a;Mitter et al, 2006;Nicol et al, 2007;Li et al, 2008;Dyer et al, 2009;Gargouri-Kammoun et al, 2009;Yang et al, 2010;Poole et al, 2012). Most of these studies found that F. pseudograminearum and F. culmorum were the most pathogenic species, and F. avenaceum, F. equiseti and F. poae were the least pathogenic species.…”
Section: Introductionmentioning
confidence: 99%